Introduction to NJWLS 2018-3 - Buch, Anders (Nordic Journal of Working Life Studies, 2018)
This issue contains nine fascinating articles that reflect on central issues in contemporary working life in the Nordic countries. The articles deal with empirical issues in relation to gender, work life quality, professionalization, unions, organizational intervention, industrial relations, and the authors adopt different theoretical and methodological frameworks in their research.